2003
DOI: 10.1002/art.11015
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of leflunomide in patients with active rheumatoid arthritis: A five‐year followup study

Abstract: Results. A total of 214 patients (mean age 57 years) were treated with leflunomide for >2 years; 74.8% of the patients were female. The mean disease duration was 4.1 years (range 0.1-26.6 years), and in 44% of patients, RA was first diagnosed within 2 years of entry into the phase III studies. The mean duration of leflunomide treatment was 4.6 years (range 2.8-5.8 years), and 32% of patients had received no previous treatment with disease-modifying antirheumatic drugs. ACR20, ACR50, and ACR70 response rates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(59 citation statements)
references
References 17 publications
(36 reference statements)
2
52
0
5
Order By: Relevance
“…with methotrexate was the reason for non continuous use. [20][21][22] Quality of life studies, XConsidering the refractory nature of the acceptance of combination by 6 (7%) ray evaluation and maximal signal intensity patients included and lack of an alternative patients. With leflunomide alone for three enhancement by dynamic gadoliniumtreatment and financial constraints, months, EULAR criteria showed improvement enhanced magnetic resonance imaging, have leflunomide can be considered an effective in 6 (54%) and remission in 1 (9%), supported its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…with methotrexate was the reason for non continuous use. [20][21][22] Quality of life studies, XConsidering the refractory nature of the acceptance of combination by 6 (7%) ray evaluation and maximal signal intensity patients included and lack of an alternative patients. With leflunomide alone for three enhancement by dynamic gadoliniumtreatment and financial constraints, months, EULAR criteria showed improvement enhanced magnetic resonance imaging, have leflunomide can be considered an effective in 6 (54%) and remission in 1 (9%), supported its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical trials have evaluated the efficacy and safety of leflunomide in patients with rheumatoid arthritis (RA) (2)(3)(4). The evidence available to date does not suggest that leflunomide leads to an increased likelihood of lung problems.…”
Section: Risk Of Interstitial Lung Disease Associated With Leflunomidmentioning
confidence: 99%
“…Leflunomide inhibits dihydroorotate dehydrogenase, a key enzyme of the pyrimidine synthesis in activated lymphocytes. It was shown that leflunomide reduces signs and symptoms of RA with regression in structural damage [7].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on Japanese patients treated with leflunomide, fatal interstitial lung disease was reported as a rare side effect of leflunomide [5,6]. However, other studies failed to confirm this side effect of leflunomide [7]. It was reported that peripheral nodule development and an increase in the number of nodules were observed in patients with RA received leflunomide therapy [8].…”
Section: Introductionmentioning
confidence: 99%